Ptosis in childhood: A clinical sign of several disorders. Issue 36 (September 2018) - Pavone, P.; Cho, Sung Yoon; Praticò, A.D.; Falsaperla, R.; Ruggieri, M.; Jin, Dong-Kyu
Abstract : Abstract: Blepharoptosis (ptosis) is a common but often overlooked sign that may serve as a sign/manifestation of other conditions, ranging from a mild and purely cosmetic presentation to a severe and occasionally progressive disorder. Ptosis may show an acute onset or may manifest as a chronic disorder. Its presentation may vary: unilateral versus bilateral, progressive versus non-progressive, isolated versus complex which occurs in association with other symptoms, and congenital versus acquired (often concomitant with neuromuscular disorders). Congenital ptosis includes the isolated type—the congenital cranial dysinnervation disorders, which are further, distinguished into different subtypes such as Horner syndrome (HS), and ptosis as a sign/manifestation of various congenital malformation syndromes. In this article, we review the primary causes of ptosis occurring in childhood, and its various clinical presentations, including a short report on selected cases observed in our institution: a classical isolated familial ptosis comprising 14 members over 5 generations, 3 sibling with isolated congenital ptosis who in addition suffered by episodes of febrile seizures, a patient with Duane retraction syndrome who presented congenital skin and hair anomalies, and a girl with HS who showed a history of congenital imperforate hymen. A flowchart outlining the congenital and acquired type of ptosis and the clinical approach to the management and treatment of children with this anomaly is reported.